Detection of SARS‐CoV‐2 in saliva and characterization of oral symptoms in COVID‐19 patients. (19th October 2020) - Chen, Lili; Zhao, Jiajia; Peng, Jinfeng; Li, Xiaoshuang; Deng, Xuliang; Geng, Zhi; Shen, Zhenyu; Guo, Fengyuan; Zhang, Qianwen; Jin, Yang; Wang, Lin; Wang, Songlin
Abstract: Objectives: In order to provide a more comprehensive understanding of the effects of SARS‐CoV‐2 on oral health and possible saliva transmission, we performed RNA‐seq profiles analysis from public databases and also a questionnaire survey on oral‐related symptoms of COVID‐19 patients. Materials and methods: To analyse ACE2 expression in salivary glands, bulk RNA‐seq profiles from four public datasets including 31 COVID‐19 patients were recruited. Saliva and oropharyngeal swabs were collected. SARS‐CoV‐2 nucleic acids in saliva were detected by real‐time polymerase chain reaction (RT‐PCR). Additionally, a questionnaire survey on various oral symptoms such as dry mouth and amblygeustia was also carried out on COVID‐19 patients. Results: ACE2 expression was present at detectable levels in the salivary glands. In addition, of four cases with positive detection of salivary SARS‐CoV‐2 nucleic acids, three (75%) were critically ill on ventilator support. Furthermore, we observed the two major oral‐related symptoms, dry mouth (46.3%) and amblygeustia (47.2%), were manifested by a relatively high proportion of 108 COVID‐19 patients who accepted the questionnaire survey. Conclusions: This study confirms the expression of ACE2 in the salivary glands and demonstrates the possibility of SARS‐CoV‐2 infection of salivary glands. Saliva may be a new source of diagnostic specimens for critically ill patients, since it can be easily collected without any invasive procedures. In addition, dry mouth and amblygeustia can be considered as initial symptoms of COVID‐19 infection. Abstract : In this study, based on the confirmation of ACE2 receptor expression in salivary glands through database analysis, it was assumed and confirmed that RNA of SARS‐COV‐2 could be detected in saliva samples. At the same time, we also clinically observed that the initial oral‐related symptoms of SARS‐COV‐2 infection may be amblygeustia and dry mouth.